A framework implementation for information accuracy in mobile commerce / Emafazzila Baharudin - Baharudin, Emafazzila (2007)
Mobile commerce (m-commerce) can be refer is a monetary value transaction that conducted via a mobile network. Mobile Commerce enables new mode of information exchange and purchases and it presents an unexplored domain with more convenient for "anytime-anywhere". With the rapid growth in wireless technologies and handheld devices, M-commerce offers significant benefits and new opportunities to user, developer, providers and the business itself One major for effective m-commerce is to deliver relevant information to the right people at the right time in the right way. The information provided in these applications should be accurate, informative and updated. Lack of consumer trust is the most significant long-term to become a viable in the business they must overcome the problems of user distrust even though mobile devices, thus these applications must deliver accurate information to the users. Towards this research, the enhancements of mobile commerce framework for information accuracy will be purposed. Before that several existing frameworks applied towards mobile commerce will be identified. Lastly, it will look-into limitations of the information accuracy from ethics and security perspective. Research approaches used are the preliminary study, knowledge acquisition, knowledge abstraction and knowledge representation to complete this project. The information is gained from the interview Avith people who are involved in these services and also from the secondary data.